IV.—The Supposed Glacial Origin of Carboniferous Terraces - Dakyns, J. R. (Geological Magazine, 1877)
There is a homely saying, “Sauce for the goose is sauce for the gander.” Mr. Goodchild, with that ingenuity for which he is remarkable, has written an elaborate paper to prove that the terraces of the Yorkshire Limestone dales are all the work of the Great Ice Sheet. This paper will doubtless call forth a number of equally elaborate answers: and this is well. But if Mr. Goodchild has a fine goose fattened on the Limestone terraces of Wensleydale, I have an equally fine gander reared on Gritstone terraces in Derbyshire: and if a frozen sauce of regelated snow from wintry storms of the Great Ice Age is good for one, it is equally good for the other. Dropping metaphor, there is no difference between terraces, mainly of limestone, in Wensleydale, and other terraces, chiefly of grit, that are found over all the Millstone Grit area of South Yorkshire and Derbyshire, saving that while limestone predominates in the one, beds of grit do in the other.